PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. AMBRA WARNA KEMASAN BOGOR - Junaedi; Dede Andi (Journal of Research and Publication Innovation, 2025)
This reasearch aims to determine the effect of motivation and work discipline on employee performance at PT Ambra Warna Kemasan Bogor. The method used is using quantitative methods. The population in this study were employees of PT Ambra Warna Kemasan Bogor with a total of 80 employees. The sampling technique used is non-probability sampling, the sampling method uses saturated sampling. the research sample was 80 respondents. The data analysis method used in the study includes instrument test consisting of validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test, simple linear regression test, multiple linear regression test, correlation coefficient, hypothesis testing consisting of determination coefficient test, partial t test and simultaneous f test. From the results of this study it can be concluded that motivation has a positive and significant influence on employee performance, the value of ????ℎ???????????????????? > ???????????????????????? or (7.809 > 1.991) with a significance value of 0.000 <0.05. Work discipline has a positive and significant effect on employee performance with a value of ????ℎ???????????????????? > ???????????????????????? or (12.563 > 1.991) with a significance value of 0.000 < 0.05. Motivation and work discipline have a positive and significant influence on employee performance with a value of ????ℎ???????????????????? > ???????????????????????? or (98.625 > 3.114) with a significance value of 0.000 < 0.05. Motivation and work discipline on employee performance have a regression effect Y = 5.088 + 0.268 X1 + 0.497 X2 + α. The resulting R-square value (coefficient of determination) was  71.9%, while the remaining 28.1% was influenced by other factors or variables that were not studied.